Detection of RSV in children ≤2 years from SARS CoV-2 negative samples at National Public Health Laboratory, Nepal - Jha, Runa; Jha, Priya; Chaudhary, Lok Bandhu; Shrestha, Lilee (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Respiratory syncytial viruses also known as human Respiratory syncytial viruses (HRSV) are highly transmissible respiratory pathogens & the leading cause of hospitalization due to lower respiratory infection, especially in the pediatric population. This study is intended to determine the RSV positivity in SARS-CoV-2 negative samples obtained from patients ≤ 2 years, collected from September 2021 to December 2021, when RSV infection is more common.Method: SARS-CoV-2 negative archived nasopharyngeal samples of children ≤2 years from September 2021 to December at National Public Health Laboratory were tested for RSV by real-time reverse transcriptase Polymerase Chain Reaction (RT-PCR) using CDC RSV Kit. The Pan -RSV primer/probe set used for the universal detection of RSV and duplex RSV subgroup primer/probe set used for the detection and subgroup-specific identification of RSV A and B.Result: A total of 294 SARS- CoV-2 negative samples from children less than 2 years were tested. RSV A was identified in 100/294 (34%) and RSV B was detected in 6/294 (2%) samples. In all, 106/294 (36%) samples were positive for RSV. Here we report RSV positivity rate of 36% in SARS-CoV-2 negative samples which were left undiagnosed during the surge of COVID-19 cases.Conclusion: Our study thereby highlights the need for an accurate and rapid differential or multiplex kits for screening respiratory disease for the effective disease management in the pediatric population.